Readership survey: the case of a research compendium in Bangla - Ullah, AKM Ahsan; Ahmed, Hasan Shareef (BRAC Research and Evaluation Division (RED), 2019)
Nirjash, a research compendium in Bangla, is published primarily for BRAC field staff. After three years of its publication it was felt essential to conduct a readership survey on its usefulness, accessibility and readability. The study assessed the readership of this compendium among the BRAC field staff. Data were collected from 1 ,698 field staff of 1 03 BRAC area offices in 18 districts. Of the 1, 698 respondents, 497 were interviewed and information from the rest (1,201) was obtained through postal questionnaires. Findings of the study revealed that 45% of the respondents were aware of Nirjash and of them 79% (604) had read it. A higher proportion of the field managers were aware of Nirjash (90%) while it was much lower (40%) for the programme organizers (PO). Among those who read it 48% found its language easy while only 7% found hard, and 93% reported to be benefited. On the contrary, nearly 2% did net like it while 40% and 58% viewed it as a very good and good to read respectively. Over the three years, readership increased by 26% compared to the survey of 1995. No field offices were found to have got all issues of the Nirjash. The study shows that there was a communication gap among the field managers and their staff and there was a problem in the distribution system.